When officials break the laws an investigative study on the illegal operation of slaughterhouses in Quezon City - Reginio, Mark Kevin Prieto; Chua, Yvonne T. (2018)
"This undergraduate thesis enumerated the violations the Mega Q Mart Slaughterhouse, Labudahin Abattoir, and the Novaliches Slaughterhouse in Quezon City have committed which hindered them from acquiring a franchise, and uncovered the reasons behind the illegal operation of the abattoirs such as the weak regulatory powers of the local government. Under the Local Government Code of 1991 and the Quezon City Revised Veterinary Code of 2016, an owner must secure a franchise to establish, construct, operate and maintain a slaughterhouse. Furthermore, a franchise is required for the issuance of a business permit. Guided by Hegel's Bureaucratic Theory, the Public-office Centered Approach, and the Rational Choice Theory, this study explained the mechanisms the Quezon City government is providing to ensure food security and food safety in the city, and the welfare of its constituents. Using a heavily qualitative approach and investigative techniques such as the people and paper trail, and first-hand observation of the abattoirs, this research proved that the poor implementation of ordinances and the weak regulation of the operation of slaughterhouses led to the illegal operation of the three slaughterhouse. The findings are presented in a three-part journalistic report with a sidebar."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Slaughtering and slaughterhouses -- Quezon City -- Philippines